(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Fahr’s disease (FD) is a progressive and degenerative familial autosomal dominant, rare neurological disorder, characterized by bilateral calcifications in the brain. FD may have neurological manifestations corresponding to the area of the brain involved. Significant proportions have neuro-psychiatric symptoms and psychosis is one. There is no specific treatment for FD but the neuropsychiatric manifestations can be managed. We present a case of a 30-year-old male with a 12-year history of psychosis, an episode of mania with psychotic symptoms, and an unsteady gait for 3 years. Baseline investigations were normal and MRI of the brain showed bilateral calcification involving significant brain areas suggestive of FD. He was managed with antipsychotics and antiepileptics. This case highlights the need for neuroimaging in cases of psychosis with neurological symptoms and puts forward the possibility of FD causing psychosis in this case.